Pengidentifikasian Citra Ikan Berformalin Dengan Menggunakan Metode Multilayer Perceptron - Wanti, Eka Pirdia; Muhathir, M (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
The richness of Indonesia's natural resources in the marine area, makes the sea an ecosystem of the existing diversity of fish. Fish is one of the types of animal protein that can be consumed by humans. Fish also contains essential vitamins and amino acids needed by the body with a biological value of up to 90% with binding tissue that makes it easier for the body to digest them. With the large number of fish that fishermen get per day, fish traders also have to make the fish they sell durable, one of which is by preserving fish with formaldehyde. Formlain is also a dangerous substance if used for food, this is because this substance can cause death if consumed long term. So that the existing problems encourage the author to identify formalin fish images using the MLP (Multilayer Perceptron) method which is a fairly reliable method in the image detection process because the search process is very directional (paying attention to backpropagation) where the feature extraction used is GLCM ( Gray Level Co-Occurrence Matrix). From this study, it was found that the Accuracy value was 62%. Where the error rate is 50%. Recall is 85%, application is 39%, precisson is 58% and F1 score is 71%.